Understanding rehabilitation in Ukraine from the perspective of key informants. Issue 2 (16th January 2020) - Archer, Anya; Harper, Lisa; Cameron, Debra
Abstract: Background: The evolution of healthcare in Ukraine has been impacted by a number of factors, including years of communist control followed by the birth of an emerging democracy and most recently, conflict in the eastern part of the country. Rehabilitation is an aspect of Ukraine's healthcare system that is still heavily influenced by the Soviet-era mentality of perfectionism. Methods: This article presents the results of a qualitative research study that undertook 13 key informant interviews to answer the question of what can be learned from the perspectives of individuals in Ukraine or with experience working in Ukraine with respect to developing and implementing appropriate rehabilitation that is inclusive and targets health equity. Results: Key themes that informants determined will affect the future of rehabilitation in Ukraine include the current health care structure, the culture surrounding disability, international and domestic sources of involvement, and a revised curriculum for new and existing rehabilitation professionals. Conclusions: The input from these individuals, supported by evidence from the literature, provides a foundational understanding of the currently fragmented rehabilitation system in Ukraine and the factors that professionals prioritize as integral components of an infrastructure that supports rehabilitation in the twenty-first century. Implications for Rehabilitation: While the recent conflict in Eastern Ukraine has served as a lightning rod to shed light on the lack of resources allocated toward disability and chronic care in the region, rehabilitation is also lacking in the general population, requiring a response that addresses the unique needs of a population of over 44 million individuals. Alongside a curriculum that complies with international accreditation standards, an influx of job and career opportunities developed by the government is needed to encourage individuals to work in the rehabilitation sector. A nation-wide strategy must be developed to disseminate knowledge about disability and rehabilitation in order to begin to address the issues of social exclusion and stigma associated with disability in many post-Soviet countries.